Effect of Age and Gender on QRS Complex Amplitude in Healthy Adults. - Khaleel, Yasir M.; Al-Selevany, Baybeen K.; Mahmood, Muzahim F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: There is controversy about the upper normal value of QRS complex amplitude in adult population under the age of 40 years. Most of the left ventricular hypertrophy voltage criteria were designed or tested for people above 40 years. In addition to age, QRS amplitude is also affected by gender and racial factors. Objectives: To evaluate the impact of age on QRS amplitude in each gender separately in healthy adults. Patients and Methods: Electrocardiograms from 563 overtly healthy adults (386 male and 177 female) aged 18-40 years were obtained using Cardios PC based ECG machine, 12-lead ECGs were recorded and QRS amplitude was measured as the sum of (SV1+RV5) and (SV2+RV6) both by computer and manual revision. The mean QRS amplitude was calculated for the entire study sample and then for each sex separately. The mean QRS amplitude was then compared between the two genders and in different age groups in the study sample. Linear regression lines of QRS amplitude versus age were drawn for each gender separately. Results: The mean ± SD of QRS amplitude in the study sample was within normal range. Also It was found that males have significantly higher mean QRS amplitude than females (p=0.001), and there was highly significant decline in mean QRS amplitude with increasing age group in the study sample (p=0.001). Linear regression lines of QRS amplitude versus age in each gender separately have shown that males have greater QRS amplitude than females and there was a clear decline in QRS amplitude with increased age from 18- to- 40 years in males, but the picture was different in females as they have shown a very slight increase in QRS amplitude with increased age from 18- to- 40 years. Conclusions: The mean QRS amplitude in males was significantly higher than females. There was a clear decline in QRS amplitude with increased age from 18-40 years in males ‘on the contrary, in females there was a very slight increase in QRS amplitude with increased age from 18-40 years.